EFEKTIFITAS PENERAPAN FLIPPED CLASSROOM DAN JUMPING TASK DI SMAN 15 PADANG - MUHAR DANTIN (JURNAL BUANA, 2021)
This study aims to determine the effectiveness of the implementation of the Flipeed Classroom and the Jumping Task is reviewed from the aspect of learning outcomes. This type of research is classified in experimental research, This research aims to assess the effect of an educational treatment or action on a student's behavior about the or whether or not the effect of that action when we compare it to other actions.The subjects of this study were students of class IX IPS at SMA 15 Padang. The data collection techniques used were observation and simple random sampling technique. The results showed that the average results of final test study (Postest), amounted to 83.47 for experiment classes and 77.74 for control classes. Based on the test t use SPSS software for pretest with α = 0.05 if the sig value is 199 > 0.05 then there is no significant difference. For (Postest) otherwise if signification 0.00 < α = 0.05 then there is a significant difference. So this learning model can be applied in improving students' learning outcomes